2015
DOI: 10.1007/s11136-015-1137-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in life-space mobility and quality of life among community-dwelling older people: a 2-year follow-up study

Abstract: Changes in life-space mobility and quality of life among community-dwelling older people: a 2-year follow-up study Rantakokko, Merja; Portegijs, Erja; Viljanen, Anne; Iwarsson, Susanne; Kauppinen, Markku; Rantanen, Taina Rantakokko, M., Portegijs, E., Viljanen, A., Iwarsson, S., Kauppinen, M., & Rantanen, T. (2016). Changes in life-space mobility and quality of life among communitydwelling older people: a 2-year follow-up study. RESULTS:The mean life-space score at baseline was 63.9±SD 20.6 and mean QOL sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 44 publications
3
107
1
4
Order By: Relevance
“…This may have important health benefits, as leaving the home is the single most important factor for increasing physical activity among older people [27]. In particular, goals related to being active, exercising, and maintaining functioning may benefit the quality of life of older people by enabling them to maintain a wider life-space [9,10]. On the contrary, lack of interest in moving outside the home may result in some older people spending time mainly at home [4], inevitably leading to sedentary behavior [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have important health benefits, as leaving the home is the single most important factor for increasing physical activity among older people [27]. In particular, goals related to being active, exercising, and maintaining functioning may benefit the quality of life of older people by enabling them to maintain a wider life-space [9,10]. On the contrary, lack of interest in moving outside the home may result in some older people spending time mainly at home [4], inevitably leading to sedentary behavior [27].…”
Section: Resultsmentioning
confidence: 99%
“…Higher life-space mobility has been associated with sense of autonomy [8], extraverted personality, social activity, and orienting more toward the future instead of only the present day [4]. Higher lifespace mobility correlates with better quality of life [9,10], and may even decrease the risk of frailty and mortality [11]. Consequently, finding ways to maintain or increase life-space mobility could contribute to well-being in old age.…”
Section: Introductionmentioning
confidence: 99%
“…The study design and methods have been published previously. 20,21 Briefly, a random sample of 2550 was drawn from the population register. These persons were informed about the study by a letter and interviewed over the phone to determine interest and eligibility for participation (living independently, able to communicate, residing in recruitment area and willing to participate).…”
Section: Methodsmentioning
confidence: 99%
“…The study design, methods and non-response analyses have been reported in detail previously (9,17). Briefly, a random sample of 2550 community-dwelling-75-to 90-year-old residents of the municipalities of Jyväskylä and Muurame was drawn from the national population register.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Decline in life-space mobility is associated with adverse health events, such as increased use of health services (6), nursing home admissions (7) and even mortality (8). Such decline is also associated with decline in quality of life in the community-dwelling general population (9). While decline in life-space mobility is common with increasing age, some people are able to maintain their life-space mobility despite chronic diseases or age-related changes in physical functioning (5).…”
Section: Introductionmentioning
confidence: 99%